Penerapan Algoritma Kriptografi Advanced Encryption Standard 128 Pada Laporan Transaksi Di Kopi Tuku - Mufti, Mufti; Wiharto, Yudi; Subandi, Subandi (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2025)
Data security is an important aspect in information management, especially in business transactions involving sensitive data such as financial reports. This study aims to apply the Advanced Encryption Standard (AES) 128-bit cryptographic algorithm to transaction report data at Kopi Tuku. AES 128-bit was chosen because of its ability to provide strong and efficient data encryption, with a high level of security and adequate processing speed. In this study, transaction data was taken from the Kopi Tuku sales system and encrypted using AES 128-bit to protect sensitive information from unauthorized access. The encryption and decryption processes were tested to ensure data integrity and security. The results showed that the implementation of AES 128-bit successfully maintained the confidentiality and security of transaction data without reducing system performance. This study concludes that the AES 128-bit algorithm is an effective solution to improve transaction data security in the coffee industry, especially in small and medium-sized businesses such as Kopi Tuku.